Active withdrawal of corticosteroids using tocilizumab and its association with autoantibody profiles in relapsed Takayasu arteritis: a multicentre, single-arm, prospective study (the Ab-TAK study) - Shirai, Tsuyoshi; Ishii, Tomonori; Okazaki, Soshi; Shirota, Yuko; Ishii, Yusho; Sato, Hiroko; Fujii, Hiroshi (Frontiers in Immunology, 2025)
ObjectivesThe feasibility of corticosteroid withdrawal (CW) for Takayasu arteritis (TAK) remains uncertain. Two autoantibodies (Abs) are identified against endothelial protein C receptor (EPCR) and scavenger receptor class B type 1 (SR-BI) in TAK, determining its three subgroups. This study aimed to evaluate CW using tocilizumab (TCZ) and its association with the Ab profile.MethodsThis prospective study, lasted for 24 weeks, included patients with relapsed but stable TAK. Scheduled tapering of prednisolone (PSL) was performed with subcutaneous TCZ (CW at week 20). The primary endpoint was the difference in type A remission, defined by CW and the absence of inflammatory signs, according to the Ab profile at week 24.ResultsTwenty patients were included and 18 patients with a mean PSL dose of 4.9 ± 2.8 mg/day were analysed. Anti-EPCR Ab-positive (E+), anti-SR-BI Ab-positive (S+), and double-negative (DN) groups included four (22.2%), eight (44.4%), and six (33.3%) patients, respectively. At week 24, the mean PSL dose was 2.0 ± 2.7 mg/day. Type A remission was observed in eight patients (44.4%), with significant differences based on the Ab profile: E+ (three patients, 75%), S+ (five patients, 62.5%), and DN (zero patients, 0%) (P=0.018). Besides, age, disease duration, PSL dose, type V arterial lesion, arterial dilation, and C-reactive protein >0.01 mg/dL were identified as risks for CW failure.ConclusionCW using TCZ was achieved in 44.4% of patients with TAK relapse and was significantly higher in E+ and S+ patients. CW can be a feasible target, and the precise selection of patients is critical.